Pengaruh Likuiditas, Profitabilitas, Solvabilitas Terhadap Harga Saham Perusahaan Otomotif Di Bursa Efek Indonesia (BEI) Tahun 2016 - 2020 - Risaldy Rizkhy Himawan; Heri Prabowo; Sutrisno Sutrisno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The automotive industry has looked quiet in recent years, this industry is not as busy as other sectors such as the property sector, mining or the financial sector. The aim of this research is to find out and analyze or provide empirical evidence regarding liquidity, profitability and solvency on automotive company share prices. Data collection in this research uses documentation techniques to obtain data. The data in this research comes from the IDX regarding company financial reports taken in 2016 - 2021. The data collection method is the classic assumption test. Prerequisite tests or classic assumptions (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), model test (ANOVA), hypothesis test (multiple linear regression analysis, partial test). Based on the results of the liquidity projection t test with a significant Current Ratio (CR) of 0.028, which means it is smaller than the normal value of 0.05, it can be concluded that there is an influence on share prices. For profitability, the projected Earning Per Share (EPR) is significant at 0.823, which means it is greater than 0.05, so it can be concluded that profitability has no significant effect on share prices. For solvency, the projected Debt to Equity Ratio (DER) has a significance of 0.032, which means it is smaller than 0.05, so it can be concluded that solvency has an effect on share prices.